2021
DOI: 10.3390/cells10061459
|View full text |Cite
|
Sign up to set email alerts
|

A Distinct Faecal Microbiota and Metabolite Profile Linked to Bowel Habits in Patients with Irritable Bowel Syndrome

Abstract: Patients with irritable bowel syndrome (IBS) are suggested to have an altered intestinal microenvironment. We therefore aimed to determine the intestinal microenvironment profile, based on faecal microbiota and metabolites, and the potential link to symptoms in IBS patients. The faecal microbiota was evaluated by the GA-mapTM dysbiosis test, and tandem mass spectrometry (GC-MS/MS) was used for faecal metabolomic profiling in patients with IBS and healthy subjects. Symptom severity was assessed using the IBS Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 63 publications
(116 reference statements)
6
40
0
Order By: Relevance
“…Other studies have found Ruminococcus to be increased in IBS patients, suggesting even a potential role as a biomarker of this disorder [56] . Interestingly, this represents a potential attractive therapeutic target in IBS, as suggested by a recent study showing that Lactobacillus paracasei CNCM I-1572 improves symptoms, modulates gut microbiota structure and function through the reduction of Rumicococcus with consequent increased levels of acetate and butyrate, and reduces intestinal immune activation in patients with IBS [57] .…”
Section: Function Of the Gut Microbiota In Ibsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have found Ruminococcus to be increased in IBS patients, suggesting even a potential role as a biomarker of this disorder [56] . Interestingly, this represents a potential attractive therapeutic target in IBS, as suggested by a recent study showing that Lactobacillus paracasei CNCM I-1572 improves symptoms, modulates gut microbiota structure and function through the reduction of Rumicococcus with consequent increased levels of acetate and butyrate, and reduces intestinal immune activation in patients with IBS [57] .…”
Section: Function Of the Gut Microbiota In Ibsmentioning
confidence: 99%
“…A recent technical review on the role of probiotics in the management of gastrointestinal disorders by the American Gastroenterology Association found that there was either insufficient evidence to recommend the use of probiotics as a part of clinical practice or a significant knowledge gap precluding any conclusions [70,71] . Although the most recent international guidelines suggest against the use of probiotics for the treatment of global IBS symptoms [12,70,71] or only in the context of a clinical trial, recent well-performed trials using well-defined end-points as recommended by the European Medicines Agency (EMA) show promising results in patients with IBS [57,72] . Based on these data, the most recent British Society of Gastroenterology guidelines on the management of IBS suggest that probiotics may be an effective treatment for global symptoms and abdominal pain in IBS, although a specific species or strain could not be recommend [29] .…”
Section: Pre-and Pro-bioticsmentioning
confidence: 99%
“…On the contrary, Ahluwalia et al (2021) did not notice any differences between the fecal microbiota of IBS and healthy individuals. They concluded the variations were likely related to microbiota functionality rather than composition [ 69 ]. Moreover, Dlugosz et al (2015) reported no significant differences in the small intestine microbiota of IBS and healthy subjects [ 70 ].…”
Section: Intestinal Microbiota In Patients With Irritable Bowel Syndromementioning
confidence: 99%
“…Complex interrelationships govern the dynamic interactions between gut microbes, host metabolomics, and exogenous drivers of disease outcome [1][2][3][4]. Irritable bowel syndrome, obesity, metabolic disorders and malignancies linked to gut dysbiosis and altered microbial diversity might be ameliorated via novel biotherapies and bioactive food constituents [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Complex interrelationships govern the dynamic interactions between gut microbes, host metabolomics, and exogenous drivers of disease outcome [1][2][3][4]. Irritable bowel syndrome, obesity, metabolic disorders and malignancies linked to gut dysbiosis and altered microbial diversity might be ameliorated via novel biotherapies and bioactive food constituents [1][2][3][4]. Metabolomic approaches have been adopted in human intervention trials, as in the case of urinary biomarkers of spinach (SPI) intake associated with the health benefits of green leafy vegetables [5], but the methodologies are not well established in target tissues of the gastrointestinal tract or following systemic uptake.…”
Section: Introductionmentioning
confidence: 99%